2018
DOI: 10.1097/md.0000000000011095
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces endoplasmic reticulum stress-associated apoptosis in human papillary thyroid carcinoma BCPAP cells via disruption of intracellular calcium homeostasis

Abstract: Background:Thyroid cancer is the most common endocrine tumor. Our previous studies have demonstrated that curcumin can induce apoptosis in human papillary thyroid carcinoma BCPAP cells. However, the underlined mechanism has not been clearly elucidated. Endoplasmic reticulum (ER) is a major organelle for synthesis, maturation, and folding proteins as well as a large store for Ca2+. Overcoming chronically activated ER stress by triggering pro-apoptotic pathways of the unfolded protein response (UPR) is a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 44 publications
1
64
1
Order By: Relevance
“…31 Apoptosis is an important way of cell death in the body. 31 Apoptosis is an important way of cell death in the body.…”
Section: Discussionmentioning
confidence: 99%
“…31 Apoptosis is an important way of cell death in the body. 31 Apoptosis is an important way of cell death in the body.…”
Section: Discussionmentioning
confidence: 99%
“…The migration capacity of HIEC‐6, SW480 and HT‐29 cells was measured by Wound healing assay. Mitomycin C (10 μg/mL) was used to inhibit cell replication . Cells were incubated in a 24‐well plate at a density of 5.6 × 10 6 cells and cultured at 37°C to form monolayer cells.…”
Section: Methodsmentioning
confidence: 99%
“…It had various chemopreventive properties, such as antioxidant, antitumoral, antiviral, antiinflammatory, antihepatotoxic, antidiabetic, hypolipidemic, and neuroprotective properties [78][79][80][81][82]. Several studies have also revealed that curcumin induced PTC cell BCPAP apoptosis and cell arrested at the G2/M phase with the concentration increased involving in multitargeting mechanisms, including the activation of reactive oxygen species (ROS)-independent DNA damage by recruiting ATM-mediated Chk2-Cdc25C-Cdc2 pathway [33], the activation of endoplasmic reticulum (ER) stress by disrupting intracellular calcium homeostasis [34], the inhibition of the β-catenin pathway [35], and the modulation of the mitochondrial Bcl-2/Bax pathway [36]. Furthermore, curcumin inhibits invasion and metastasis in PTC cells by upregulating E-cadherin expression and downregulating matrix metalloproteinase-9 (MMP-9) [37].…”
Section: Tannins (Phenolic Acids)mentioning
confidence: 99%